Complete Genome Sequence of Salmonella enterica Serovar Typhimurium Siphophage Skate - Rohren, Matthew (Microbiol Resour Announc, 2019)
Salmonella enterica serovar Typhimurium is a Gram-negative pathogen and a primary cause of foodborne illnesses worldwide. Here, we present the complete 47,393-bp genome sequence of the siphophage Skate, which was isolated against S. Typhimurium strain LT2.